2021
DOI: 10.7759/cureus.14968
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Hypertriglyceridemia-Induced Acute Pancreatitis in a Patient With Diabetic Ketoacidosis

Abstract: Diabetic ketoacidosis (DKA) with coexisting hypertriglyceridemia-induced acute pancreatitis is a rare yet potentially life-threatening condition. This report describes a patient with no history of diabetes who presented with DKA and coexisting acute pancreatitis secondary to severe hypertriglyceridemia. The patient did not respond to standard DKA management or plasmapheresis, developed acute respiratory distress syndrome (ARDS), and eventually expired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Patients diagnosed with acute pancreatitis and DKA had higher levels of HTG and more extended hospital stays and complications compared to those without DKA [7]. Narala et al have described a case of acute pancreatitis induced by HTG concurrent with DKA as an initial manifestation of type 2 DM [8]. Naqvi S et al reported a case of the life-threatening triad of acute pancreatitis, DKA, and HTG due to poor compliance with DM treatment measures [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients diagnosed with acute pancreatitis and DKA had higher levels of HTG and more extended hospital stays and complications compared to those without DKA [7]. Narala et al have described a case of acute pancreatitis induced by HTG concurrent with DKA as an initial manifestation of type 2 DM [8]. Naqvi S et al reported a case of the life-threatening triad of acute pancreatitis, DKA, and HTG due to poor compliance with DM treatment measures [9].…”
Section: Discussionmentioning
confidence: 99%
“…The management of HTG-induced acute pancreatitis primarily involves reducing serum triglyceride levels. This can be achieved through dietary modification, lipid-lowering medications, and, in severe cases, therapeutic plasma exchange or plasmapheresis [7,8]. Intravenous hydration, pain management, and nutritional support are essential components of pancreatitis management [9].…”
Section: Discussionmentioning
confidence: 99%